Network security through data analysis from data to action - Collins, Michael (Michael Patrick) (O'Reilly Media, Inc., 2017)
Traditional intrusion detection and logfile analysis are no longer enough to protect today's complex networks. In the updated second edition of this practical guide, security researcher Michael Collins shows InfoSec personnel the latest techniques and tools for collecting and analyzing network traffic datasets